2023
DOI: 10.2196/38065
|View full text |Cite
|
Sign up to set email alerts
|

A Safe Place to Learn: Peer Research Qualitative Investigation of gameChange Virtual Reality Therapy

Jessica Bond,
Alexandra Kenny,
Vanessa Pinfold
et al.

Abstract: Background Automated virtual reality (VR) therapy has the potential to substantially increase access to evidence-based psychological treatments. The results of a multicenter randomized controlled trial showed that gameChange VR cognitive therapy reduces the agoraphobic avoidance of people diagnosed with psychosis, especially for those with severe avoidance. Objective We set out to use a peer research approach to explore participants’ experiences with ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…A peer-led qualitative evaluation of gameChange with 20 participants, analysed without knowledge of the trial results, also found that those individuals who were struggling the most with agoraphobic avoidance gained the most benefits from gameChange ( Bond et al, in press ). The interviews captured how individuals who were housebound and low in mood were often able to do activities subsequently that they had not imagined possible at the start of the VR therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A peer-led qualitative evaluation of gameChange with 20 participants, analysed without knowledge of the trial results, also found that those individuals who were struggling the most with agoraphobic avoidance gained the most benefits from gameChange ( Bond et al, in press ). The interviews captured how individuals who were housebound and low in mood were often able to do activities subsequently that they had not imagined possible at the start of the VR therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Patients can overcome anxieties and return to everyday situations, even with a very brief therapy. As a patient in a qualitative study of gameChange described ( Bond et al, in press ): “The everyday situations that I found difficult, the more I practised them in the VR, the more I could get confident and be more confident in day-to-day life. I think because I was learning about it in the VR and practising and practising and practising, I could then take that and build up more confidence and do it in the everyday real world.” This provides great optimism for clinical services providing care to patients with severe difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…While VR serious games are gaining popularity for treating various psychological issues, for instance the treatment of anxiety in studies [16,17], our research exclusively centers on addressing the negative symptoms of schizophrenia. By focusing our work in this particular area, we want to have a significant impact on people dealing with the difficult challenges associated with schizophrenia.…”
Section: State-of-the-artmentioning
confidence: 99%